(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
In recent years, the problems of evaluating the efficiency of the labor market infrastructure have been the object of research of a number of scientists and practitioners. The purpose of the labor market and employment theory is to scientifically express the events and processes taking place in these areas and to constantly study them.